2023
DOI: 10.1007/s11356-023-30240-1
|View full text |Cite
|
Sign up to set email alerts
|

Smart waste bin monitoring using IoT for sustainable biomedical waste management

Aliyu Ishaq,
Shamsuddeen Jumande Mohammad,
Al-Amin Danladi Bello
et al.

Abstract: Suboptimal management of healthcare waste poses a significant concern that can be effectively tackled by implementing Internet of Things (IoT) solutions to enhance trash monitoring and disposal processes. The potential utilisation of the Internet of Things (IoT) in addressing the requirements associated with biomedical waste management within the Kaduna area was examined. The study included a selection of ten hospitals, chosen based on the criterion of having access to wireless Internet connectivity. The issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…They found this reduced cost and increased the efficiency of waste management [31]. Another study by Ishaq et al found that placing sensors within medical waste bins to notify the waste management team how quickly various bins became full helps with optimising placement of bins where they are most needed [32].…”
Section: Theme: Lack Of Spacementioning
confidence: 99%
“…They found this reduced cost and increased the efficiency of waste management [31]. Another study by Ishaq et al found that placing sensors within medical waste bins to notify the waste management team how quickly various bins became full helps with optimising placement of bins where they are most needed [32].…”
Section: Theme: Lack Of Spacementioning
confidence: 99%
“…The sensors are equipped with WiFi or Bluetooth connectivity, enabling the seamless transmission and processing of data acquired by the sensors or actuators in waste monitoring. (Ishaq et al, 2023) The data acquired is then stored in the cloud, enabling easy access to the requisite services. In current waste management, geospatial technology tracks transportation routes, vehicles, and waste bins.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Ishaq, et al(2023), 6 aims to investigate the potential of Internet of Things (IoT) technology in enhancing the management of biomedical waste in healthcare facilities, with a specific concentration on the Kaduna region of Nigeria. A system for intelligent refuse bin monitoring utilising IoT sensors and actuators is proposed by the author.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The gathering of waste garbage is a major problem due to tremendous increase in the population in the last few decades. 6 The waste garbage if not collected properly from the area and is left in the open surrounding then it leads to various health problems and epidemic's diseases. The municipal corporations in India which are situated in very city are responsible for waste garbage management.…”
Section: Introductionmentioning
confidence: 99%